PRINCIPIUL BIOMECANIC CE GUVERNEAZA TERAPIA IMPLANTARA - Alexandra Maria Mârţu; Norina Consuela Forna (Romanian Dental Association for Education, 2016)
The purpose of this study is to individualize the main aspects of an ideal biomechanics and its influence on the implanto-prosthetic success. We quantified the main factors of a successful implant biomechanics, represented by: pre-implant analysis, pre-implant augmentation surgery, the optimum and accurate 3D implant positioning, the management of the peri-implant soft tissues, an implant axis that is compatible with the prosthetic options, the quality of the prosthetic restoration. The biomechanical characteristics of the implanto-prosthetic complex depend on the very features of the osteo-integrated implants, on the right choice of bone and the type of occlusal charge, on the position and orientation of implants, on the type of implanto-prosthetic rehabilitation and the occlusal concepts used in restoration. In this context, the choice of the system, of the surgical protocol and of the occlusal principles applied by the clinician have both a direct and indirect influence on the intensity and distribution of occlusal forces transmitted to the implant and to the support bone. In order to minimize the stress at the level of the bone-implant interface, a thorough knowledge and accurate application of the biomechanical principle is required, starting with the type of implant.